2014
DOI: 10.1016/j.biocon.2014.09.044
|View full text |Cite
|
Sign up to set email alerts
|

A social–ecological systems approach to non-native species: Habituation and its effect on management of coqui frogs in Hawaii

Abstract: a b s t r a c tNon-native species introductions have the ability to affect both ecological and social systems, thus to address those outcomes both ecological and social influences on an invasion need to be understood. We use a social-ecological systems approach to investigate connections between human and ecological factors that affect efforts to control the non-native coqui frog (Eleutherodactylus coqui) on the island of Hawaii. The coqui frog is recognized as a 'pest' and 'injurious wildlife' by the Hawaii D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…This literature has typically focused on investigating resident involvement in IS control by understanding individuals' attitudes, values, behavioral control beliefs, and knowledge on how to control a species (Aslan et al 2009, Sharp et al 2011, Kalnicky et al 2014, McLeod et al 2015. Aslan et al (2009), for example, found that individuals' decisions to engage in control of yellow star thistle (Centaurea solstitialis L.) across private lands were influenced by lack of knowledge of proper control techniques and perceptions of lack of money and time for engaging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This literature has typically focused on investigating resident involvement in IS control by understanding individuals' attitudes, values, behavioral control beliefs, and knowledge on how to control a species (Aslan et al 2009, Sharp et al 2011, Kalnicky et al 2014, McLeod et al 2015. Aslan et al (2009), for example, found that individuals' decisions to engage in control of yellow star thistle (Centaurea solstitialis L.) across private lands were influenced by lack of knowledge of proper control techniques and perceptions of lack of money and time for engaging.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the existing literature on resident engagement in IS control has typically focused on understanding individuals' decisions to control IS on their own land (Aslan et al 2009, Kalnicky et al 2014). However, interventions may not reach all residents in a community, leaving many areas uncontrolled (Klepeis et al 2009, Epanchin-Niell et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…From a social perspective, nonnative amphibians have been blamed for noise pollution (Kalnicky et al 2014) and producing toxic chemicals that harm humans and occasionally kill pets (Krakauer 1968;Reeves 2004). Because this book is focused on terrestrial species, this chapter will review nonnative amphibians that are primarily terrestrial.…”
Section: R a N A D R A Y T O N I I R A N A P I P E N S R A N A R U G mentioning
confidence: 99%
“…These groups raised funds to rent or purchase control equipment, and invested endless hours of volunteer time monitoring and controlling populations (Anonymous 2010;Beard and Pitt 2012). Despite much local support in Hawaii for coqui suppression or eradication, there were also people that enjoyed the call of the coqui while others became accustomed to it (Kalnicky et al 2014). More speci cally, Kalnicky et al (2014) found that people with more frogs on their property and those who owned property tended to have less-negative attitudes toward the frog.…”
Section: Scope Of the Issues/damage Caused By The Speciesmentioning
confidence: 99%
See 1 more Smart Citation